Fracture strength and fractographic analysis of zirconia copings treated with four experimental silane primers - Mustafa, Ammar A.; Jukka Pekka , Matinlinna; Andy H., Choi; Abdul Razak , Abdul Aziz (Taylor and Francis, 2013)
This study evaluated and compared the effect of new four experimental silane coupling agents on ‎the fracture strength of zirconia copings. The findings were supported with fractographic and ‎finite element analyses. All together 125 zirconia copings with a wall thickness of 0.6mm were ‎fabricated on identical nickel-chromium master dies and then divided randomly into five groups ‎‎(n = 25). Four test groups were prepared according the experimental silane primer (labeled: ‎OIWA1, OIWA2, OIWA3 and OIWA4) and one ontrol group without silanization. The silane ‎monomers used were: 3-methacryloxypropyltrimethoxysilane (in OIWA1), 3-‎acryloxypropyltrimethoxysilane (in OIWA2), 3-isocyanatopropyltriethoxysilane (in OIWA3) and ‎styrylethyltrimethoxysilane (in OIWA4). Tribochemical sandblasting (silica-coating) treatment ‎was performed to the inner surface of the copings in the test groups. All the specimens were ‎silanized at the inner surfaces of the zirconia copings. Self-adhesive universal resin cement was ‎used to cement the copings to the underlying master die. Zirconia copings were vertically loaded ‎on the cusp area until the first crack failure was occurred using Precision Universal Tester at a ‎constant crosshead speed of 1 mm/min. Then, the machine was manually controlled to cause ‎more failure to further determine the texture of fracture. Three dimensional finite element ‎analysis and fractography were performed to support the fracture strength findings. Based on the ‎finite element analysis results, zirconia silanized with 3-acryloyloxypropyltrimethoxysilane ‎showed the highest fracture strength with a mean of 963.75N (SD 4.5 N), while zirconia copings ‎silanized with 3 methacryloyloxypropyltrimethoxysilane showed a mean fracture strength value ‎of 925.65N (SD 2.4 N). Styrylethyltrimethoxysilane-silanised zirconia showed mean fracture ‎strength of 895.95N (SD 3.5 N). Adding silane coupling agents to the resin-zirconia interface ‎increased the fracture strengths significantly (ANOVA, p < 0.05). Silanization with four new ‎experimental silane primers in vitro produced significantly greater fracture strength than the ‎control group not treated with the test silane.‎